Spatio-Temporal Evolution and Correlation Analysis of Urban Land Use Patterns and Air Quality in Pearl River Delta, China - Hong, Kai-rong; Qiu, Lin-shu; Yang, Dong-xiao; Jiang, Minxing (Frontiers in Environmental Science, 2021)
Urban air quality, which is related to the health of local residents, has been a hot topic among the masses and academic circles. In addition to economic growth, China's rapidly increasing urbanization rate has also brought great pressure on urban air quality, especially in the Pearl River Delta region, where due to its huge economic size and population, urban air quality has become the focus of local residents. This study first analyzed the spatio-temporal trends of land use and PM2.5 average annual concentration, which represents air quality, in the Pearl River Delta region from 2000 to 2018. Secondly, the spatial error model of the Pearl River Delta region was constructed by using spatial effect, spatial modeling theory and spatial model estimation. The spatial-temporal evolution and influencing factors of PM2.5 concentration were discussed in three dimensions of fixed time effect, fixed individual effect and fixed overall effect. The results showed that the land use in the Pearl River Delta decreased and the artificial surface increased year by year, while the PM2.5 concentration increased first and then decreased. In addition, cultivated land and forestland were negatively correlated, while grassland and water bodies were positively correlated with PM2.5 concentration. The conclusion of this study has a certain theoretical reference for urban land use planning and air quality assurance.